APLIKASI WHATSAPP GATEWAY UNTUK NOTIFIKASI SURAT PERINGATAN MAHASISWA MENGGUNAKAN METODE MESIN TURING DAN REST - Affandi, Luqman; Arhandi, Putra Prima; Wibowo, Dimas Wahyu (DINAMIKA DOTCOM, 2019)
Information technology is developing very rapidly, especially in the field of message delivery, this is marked by the development of many applications on smartphones that serve communication via the internet, one of which is Whatsapp, which makes it easier for users to send text messages and video and audio in real time using internet data packages. From these developments can be used for services and teaching and learning processes on campus. One process and service for teaching and learning that is still often hampered is a notification or notification of warning letters to students and parents of students. There are often delays in notifications because sending these letters still uses mail delivery. This delay has a negative effect on the teaching and learning process where the DPA (Academic Development Lecturers) often get protests and complaints from parents because this notice is too slow to convey. Keywords: WhatsApp, Gateway, Machine touring